Unveiling the development of sprint athletes: Percentile patterns, peak performance age, and a performance progression model - Agudo-Ortega, A.; Santos del Cerro, J.; Salinero, J. J.; Gonzalez-Rave, J. M. (Journal of Human Kinetics, 2024)
The purpose of this study was to provide percentile curves, peak performance age for all sprint distances, and two linear regression models in order to analyse the individual trajectories of Spanish sprinters to explain the achievement of the senior category. A retrospective analysis was undertaken using rankings of the Spanish Athletics Federation. We analysed 4398 sprint athletes between 2004 and 2021. Our results show that the percentile curves are farther apart as the distance increased. Peak performance age was reached earlier in males than females in all distance categories (25.31 ± 0.12 and 25.79 ± 0.70 years for 100 m, 25.45 ± 0.16 and 27.40 ± 0.31 years for 200 m, and 25.61 ± 0.24 and 27.46 ± 2.28 years for 400 m in males and females, respectively). The two linear regressions display the importance of consistent high performance in junior categories (p < 0.01; ß = -1.92 and p = 0.15; ß = -1.22, respectively) together with the best results in the U23 category (p < 0.001; ß = 0.51 and p < 0.001; ß = 0.51, respectively) to achieve participation in the senior category. We conclude that as the running distance increases, the differences between percentiles also increase, the peak performance age occurs earlier in Spanish sprinters than shown in previous research for all sprint distances, and attaining the senior category depends upon achieving the best results in previous categories and gaining extensive experience (consistent high-performance participation) in the event.